The Political Awareness in the Candidates Using Twitter. a Clusterization Exercise for the Municipal Elections in Chile 2016 [la Notoriedad Política en Los Candidatos Que Usan Twitter. Un Ejercicio de Clusterización Durante Las Elecciones Municipales en Chile 2016 - Jara-Reyes, R; Castro-Gomez, G (University of La Laguna, 2017)
Introduction. In this paper, we study the relationship between the use of Twitter and political awareness of the candidates to mayor in municipal elections on October of 2016. Methodology. Through a clustering method, we group candidates according to the individual characteristics (age, gender and study grade) and political characteristics (incumbency, political sponsorship and orientation) and their use of twitter by municipalities (tweets, retweets and favorites). Results. We put in evidence that our way to agglutinate the data is given by their political awareness / twitter use. In this sense, we see that the political profile is what allows us to group the uses of Twitter of the candidates in a more enlightening way. Conclusions. At a local territorial level, where the spectrum of candidates is broader, the use of Twitter reinforces the difference between the candidates with less political awareness. This contradicts the idea that Twitter could be an alternative for those candidates with less political awareness. © 2017, University of La Laguna. All rights reserved.